Rearing non-diapausing western spruce budworm on pre-mixed artificial diet - Mohamad, Rosli; Oloffs, Peter C. (The Entomological Society of British Columbia, 1984)
The western spruce budworm, C. occidentalis Freeman, was reared on pre-mixed artificial diet in the laboratory without diapause. The colony was maintained indefinitely with a generation time of 38-40 days. Females deposited an average of 307 eggs of which about 91% survived. The rearing technique provided a steady and reliable supply of the insects for other basic research. The supply of insects could be adjusted according to need at any particular time. Sanitation is essential to successful rearing, because contamination of diet or rearing facilities produces an unsuitable environment for the survival and development of newly-hatched larvae.